Incidência de sintomas osteomusculares em atletas das federações de jiu-jitsu do estado do Amazonas - Cavalcante, Rana de Souza (Brasil, 2023)
Jiu-jitsu means gentle art and emerged as an art of self-defense 2,500 years ago, arriving in Brazil at the end of the 19th century. In Jiu-Jitsu, blows are performed that aim to nullify the strength of the opponent, being considered a highly harmful martial art, and with great risks of SO. The aim was to identify the anatomical regions with the highest incidence of SO in athletes from the state of Amazonas jiu-jitsu federations in the last 6 months. Personal and anthropometric data will be collected through a QNSO questionnaire developed specifically for this study, due to the current pandemic scenario in the country. 51 athletes participated, 43 ♂ (85%) and 8 ♀ (15%). The regions with the highest incidence of SO in the last 6 months were: knee (63%), shoulder (57%), wrist (57%), ankle (48%) and hip (44%).